Process Integration of Production, Purification, and Immobilization of β‑Glucosidase by Constructing Glu-linker-ELP-GB System - Rong, Junhui; Han, Juan; Zhou, Yang; Wang, Lei; Li, Chunmei; Wang, Yun (Industrial & engineering chemistry research, 2018)
In enzymatic conversion of biomass, how to degrade cellulose into fermentable glucose in an economic, efficient, and clean way has become an important subject. As for the application of cellulase in cellulose degradation, the process optimization in enzyme engineering is urgently desired. The traditional multistep purification processes lead to rising production costs and reduced activity of cellulase; meanwhile, the difficulty in reusability of cellulase has also become a big baffle in the cost-effective application of cellulase in biomass degradation. In this paper, the biocatalyst Glu-linker-ELP-GB (GLEGB) containing binary tags, elastin-like polypeptide (ELP), and graphene-binding (GB), was constructed to simplify the purification and immobilization of β-glucosidase (Glu) from Coptotermes formosanus. A high recovery rate (97.2%) and purification fold (18.7) of GLEGB was obtained by only one round of inverse transition cycling (ITC) with 0.5 M (NH4)2SO4 at 25 °C in a short incubating time of 10 min. The purification performance of the one-round ITC method is superior to the commonly used Ni-NTA resin affinity method. Furthermore, the high loading amounts of GLEGB immobilized on GO (698.2 mg g–1) and C3N4 (527.3 mg g–1) were achieved by the synergistic effects of ELP and GB tags. The storage stability and thermal stability of GLEGB was significantly enhanced after immobilization. The recombinant GLEGB immobilized on GO, MGO, graphite, C3N4, C200, and C400 retained 71.4%, 69.5%, 75.1%, 61.2%, 73.5%, and 80.2% of their initial activities respectively after eight cycles. It is worth mentioning that the K m values of GLEGB immobilized on lamellar carbon materials including GO, MGO, and C3N4 are very close to free GLEGB, showing a high affinity of recombinant GLEGB to substrate. To our knowledge, this is the first report on enzyme-linker-ELP-GB system with wide application prospect in the efficient purification and immobilization of enzyme, which can achieve the goal of reducing cost and improving efficiency of biocatalyst in enzymatic conversion of biomass.